Strategies to achieve HPV-related disease control in Italy: results from an integrative approach. (13th November 2019) - Acampora, A; Grossi, A; Colamesta, V; Barbara, A; Causio, A; Calabrò, G E; Boccia, S; Cicchetti, A; de Waure, C
Abstract: Background: Vaccination against Human Papilloma Virus (HPV) might allow controlling HPV-related diseases but coverage in Italy is far from the optimal goal. This project aimed at identifying strategies to promote HPV vaccination in Italy. Methods: an integrative approach including a systematic review and a two-step panel consultation was used to identify strategies for improving coverage among adolescents who are already target of the national campaign and promote vaccination in further targets. The systematic review followed PRISMA recommendations and the panel consultation relied on the administration of questionnaires in the first step and on a televoting system during a consensus conference in the second one. Ten experts were involved belonging to Gynecology, Public Health, General Practice, Pediatrics and Consumers. Recommendations relied on a set of criteria drawn from the Evidence to Decision framework. Results: The systematic review led the identification of three main strategies to improve coverage respectively based on reminds, education and multicomponent approaches. Following the evaluation of selected criteria, namely relevance of benefits, evidence strength, feasibility, equity, acceptability and costs, a strong recommendation was formulated on the use of reminds tailored to vaccine recipients or their parents whereas a moderate one was developed on the use of reminds directed to health professionals. A moderate recommendation was released on the implementation of multicomponent interventions. The panel consultation also supported the elaboration of a strong recommendation on the promotion of vaccination among women treated for HPV-related diseases, fertile women not yet vaccinated and 25 years old women. Catch-up initiatives, in particular among women and men 18 years old, were also identified as strongly recommendable. Conclusions: This project led to identify several valuable strategies to strengthen HPV vaccination at national level. Key messages: Using reminds tailored to vaccine recipients or their parents is strongly recommended while using reminds directed to health professionals and multicomponent interventions are moderately recommended. It is strongly recommended to promote HPV vaccination among women treated for HPV-related diseases, fertile women not yet vaccinated and 25 years old women.